2003
DOI: 10.1046/j.1523-1747.2003.12252.x
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 Antisense Therapy Chemosensitizes Human Melanoma in a SCID Mouse Xenotransplantation Model

Abstract: It is well established that high expression of the antiapoptotic Bcl-2 family proteins Bcl-2 and Bcl-xL can significantly contribute to chemoresistance in a number of human malignancies. Much less is known about the role the more recently described Bcl-2 family member Mcl-1 might play in tumor biology and resistance to chemotherapy. Using an antisense strategy, we here address this issue in melanoma, a paradigm of a treatment-resistant malignancy. After in vitro proof of principle supporting an antisense mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 53 publications
4
75
1
Order By: Relevance
“…In addition to our study, Mcl-1 has recently been shown to be involved both in the chemosensitization or radiosensitization of melanoma tumors (74)(75)(76), and in resistance of other solid tumors to TRAIL-induced apoptosis (77). In melanoma, resistance to TRAIL has been rather attributed to other antiapoptotic proteins, such as c-Flip and XIAP (31,49,78).…”
Section: Discussionsupporting
confidence: 61%
“…In addition to our study, Mcl-1 has recently been shown to be involved both in the chemosensitization or radiosensitization of melanoma tumors (74)(75)(76), and in resistance of other solid tumors to TRAIL-induced apoptosis (77). In melanoma, resistance to TRAIL has been rather attributed to other antiapoptotic proteins, such as c-Flip and XIAP (31,49,78).…”
Section: Discussionsupporting
confidence: 61%
“…ELISA cell death assay showed that the chemotherapeutic agent etoposide, alone, caused remarkable apoptosis in leukemia cells. Of note, we found that the inhibition of Mcl-1 using siRNA also resulted in significant apoptosis in the absence of etoposide, which is in contrast to the finding of others on solid tumors (Thallinger et al, 2003, Thallinger et al, 2004. However, this observation is similar to that found on other studies on hematological malignancies (Hussain et al, 2007;Quinn et al, 2011), illustrating the important biological role of Mcl-1 in leukemic cells.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, Mcl-1 has been associated with melanoma progression 28 and shown to be critical for survival of melanoma cells undergoing ER stress 29 or anoikis 30 . Mcl-1 has also been implicated in mediating resistance of melanoma cells to radiation 31 and several chemotherapeutic agents [32][33][34] .…”
Section: Resultsmentioning
confidence: 99%
“…Melanoma is an example of tumours in which Mcl-1 plays crucial tumourpromoting roles by promoting survival on anoikis 30 and endoplasmic reticulum stress 29 and mediating resistance to radiation 31 and several anticancer agents such as Fas 32 , dacarbazine 33 contribution of these pathways to the observed upregulation of Mcl-1 in different types of tumours is not clear. In T-cell acute lymphoblastic leukaemia, follicular lymphoma, small cell lung carcinomas, ductal and colon adenocarcinoma, high Mcl-1 levels have mainly been attributed to decreased proteasomal degradation and increased stability of Mcl-1 protein 7,35 .…”
Section: Discussionmentioning
confidence: 99%